THE ROLE OF ETHNOECOLOGY IN SUPPORTING A GREEN ECONOMY - Yohanes Kamakaula (Yayasan Adra Karima Hubbi, 2026)
Ethnoecology is understood as a study that positions the relationship between local communities and the natural environment as a whole built through traditional knowledge, value systems, and ecological practices passed down across generations. This study aims to examine in depth the contribution of ethnoecology to supporting the implementation of a green economy, particularly through optimizing local wisdom in sustainable natural resource management. The research approach applied is qualitative, using literature review and case study methods, through a systematic review of scientific articles, policy documents, and relevant previous research findings. The research findings indicate that ethnoecological practices play a significant role in maintaining environmental sustainability, increasing the sustainability of natural resource utilization, and strengthening the economic base of local communities. Local knowledge rooted in ecological experience has been shown to encourage more environmentally friendly economic practices, reduce the rate of resource exploitation, and open up opportunities for economic development based on local potential. The analysis and discussion indicate that mainstreaming ethnoecology within a green economy policy framework can strengthen sustainable development efforts that are participatory and equitable. Therefore, this study concludes that ethnoecology is a strategic element that needs to be comprehensively integrated into the planning and implementation of development policies to support the success of a green economy.